1929. Risk of Acute Kidney Injury in Combat-Injured Patients Associated With Concomitant Vancomycin and Extended-Spectrum β-Lactam Antibiotic Use. (26th November 2018) - Yabes, Joseph; Stewart, Laveta; Shaikh, Faraz; Lu, Dan Z; Merritt, Teresa; Mende, Katrin; Carson, Leigh; Robben, Paul M; Leimbach, Robert; Petfield, Joseph L; Ganesan, Anuradha; Tribble, David R; et al.
Abstract: Background: Studies of vancomycin (VANC) and piperacillin–tazobactam (VPT) induced acute kidney injury (AKI) have included diverse populations obscuring clinical generalizations. To our knowledge, previous studies have omitted combat-related trauma patients despite frequent exposure to broad-spectrum antimicrobials. Our objective was to analyze whether combination therapy with VPT was associated with an increased risk of AKI compared with VANC and other broad-spectrum β-lactam antibiotics (VBL). Methods: Patients within the Trauma Infectious Disease Outcomes Study (TIDOS) who received ≥48 hours concomitant VPT or VBL started within 24 hours of each other were assessed. Exclusion criteria were receipt of renal replacement therapy and baseline creatinine >1.5 mg/dL or missing. Based on prior studies, AKI was defined by meeting any of the RIFLE, AKIN or Vanc Consensus Guidelines criteria 3–7 days after therapy initiation. Glomerular Filtration Rate (GFR) was calculated using Modification of Diet in Renal Disease (MDRD) equation. Results: Of 2692 patients, 39 patients who received VPT and 197 who received VBL (172 meropenem, 17 imipenem-cilastatin, and 8 cefepime) were included with median ages of 25 and 24 years old, respectively. Initial median GFRs were 138mL/minute in both groups. Gender distribution was equal with 97% males receiving VPT and 99% VBL. Thirty-five (90%) patients in VPT and 186 (94%) in VBL had an Injury Severity Score>15 ( P = 0.28). Median duration of VANC therapy was 6 and 8 days for VPT and VBL ( P = 0.36). Injuries were sustained in Afghanistan in 82% treated with VPT and 92% with VBL ( P = 0.06). The groups differed by US-based hospital ( P = 0.06), and presence of blast injury which was more common in VBL ( P < 0.001). In the VBL group, incidence of AKI was 9.1% compared with 12.8% in the VPT group ( P = 0.55). Median time to AKI was 6 days (IQR 5–6) for those receiving VPT and 4 days (IQR 3–6) for VBL. Conclusion: Recent reports of nephrotoxicity of VPT have been challenging to interpret due to multiple potential confounders. In this young and previously healthy severely ill combat-injured population, VPT was not associated with higher crude rates of AKI than VBL. This may be related to this unique patient population or sample size. Disclosures: All authors: No reported disclosures.